Connection on Events of Subclause to Main Clause: Analyzing Sentence Construction in Kyoukasho (Japanese Textbooks) - Roni, Roni; Nurhadi, Didik; Martiana, Twin D (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2023)
Abstract. Along with the rising influence of Japanese in many spheres of life, many language learners around the world have learned Japanese. Kyoukasho, which means "Japanese language textbooks," are the main books that people who don't speak Japanese use to learn Japanese. Many features of Japanese linguistics may be found in Kyoukasho, one of which is subclause construction. A compound sentence in Japanese must include linking elements. These elements connect the subclause to the main clause. As a result, the purpose of this research is to discover how Kyoukasho explains the use of connecting constituents of time in subclause to form compound sentences. Thistudy is necessary because it can assist Japanese learners in better understanding sentence construction. This was a literary study that used a descriptive-qualitative approach. To obtain the result, data were obtained from six Kyoukasho regularly used by Indonesian higher education institutions to teach Japanese and evaluated using agih and matching analytical approaches. This study drew two conclusions about the use of linking constituents: their use in the sequence of events and their use in the temporal order. There were three events completed for the sequence of events, namely: after, before, and concurrent events, and four orders concluded for the time order, namely: starting-ending, starting, ending, and neutral. Aside from this, this study discovered that the duration of the actions in the concurrent event affects the structure as well. The event is divided into three categories here: open-closed, complete, and partial.Keywords: Time Subclause, Constituents, Japanese Grammars